2020
DOI: 10.1101/2020.02.28.970228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GOT1 Inhibition Primes Pancreatic Cancer for Ferroptosis through the Autophagic Release of Labile Iron

Abstract: 2 of ferritin. In sum, our study identifies a novel biochemical connection between GOT1, 52iron regulation, and ferroptosis, and suggests the rewired malate-aspartate shuttle plays 53 a role in protecting PDA from severe oxidative challenge. 54 55

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Kremer et al [60] demonstrated that GOT1 withdrawal was reported to promote a catabolic cell state, resulting in decreased OxPHOS, activated autophagy, and ferritinophagy, which raised iron pools and promoted ferroptosis. Therefore, we assumed that autophagy is related to sepsisinduced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kremer et al [60] demonstrated that GOT1 withdrawal was reported to promote a catabolic cell state, resulting in decreased OxPHOS, activated autophagy, and ferritinophagy, which raised iron pools and promoted ferroptosis. Therefore, we assumed that autophagy is related to sepsisinduced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Classic examples of this include mitochondrial or DNA damage, such as those induced by chemotherapy and radiotherapy, and more recent nuanced examples illustrate how specific programs can be regulated by autophagy (e.g. iron homeostasis) (Mancias et al 2014;Kremer et al 2020).…”
Section: Cell-intrinsic Metabolic Mechanisms Of Therapeutic Resistancementioning
confidence: 99%